Combining Seismic Risk Analysis and Network Modeling to Assess Hospital Service Accessibility in the Bay Area, California - Kukunoor, Charan; ICASP14; Wu, Jingzhe; Lu, Xinlu; Mao, Dan; Ceferino, Luis (My University, 2023)
Earthquakes can damage hospitalsﾒ infrastructure and disrupt critical healthcare functions. For example, the Northridge Earthquake in California damaged 11 acute hospitals, and eight had to be evacuated. These disruptions affect short and long-term accessibility to healthcare across large regions through cascading effects. In this paper, we propose a framework to combine risk analysis and network science methods to evaluate the post-earthquake functionality of hospital systems. We demonstrate the frameworkﾒs applicability to the hospital system in the Bay Area, California, after a hypothetical M 7.2 earthquake on the Hayward Fault. First, we use risk analysis to estimate the post-earthquake capacities in 82 acute care hospitals in terms of the number of functional beds. Next, we combine this analysis with a graph representation of the healthcare network composed of the hospital and transportation system. We link the vulnerabilities of the hospitals to the graphﾒs edge capacities and evaluate healthcare accessibility. We demonstrate that this approach can point to the hospitals with the most risk of losing hospital functionality and receiving patients from regions without medical services. Finally, we suggest future studies evaluate multiple scenarios and quantify the uncertainties in post-earthquake accessibility to healthcare services.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED